2020
DOI: 10.1021/acsmaterialslett.0c00293
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Lithium-Ion Conduction in Gel Polymer Electrolyte by Metal-Organic Frameworks

Abstract: Gel polymer electrolytes (GPL) that comprise polymer, lithium salts, and organic plasticizers hold great promise for safer lithium-ion batteries, because of liquid-like ionic conductivity, as well as solid-like leakage-free property. However, only a small portion of ion conduction effectively carried by Li + ions (or low Li + transference number) gives rise to poor interfacial stability between GPL with electrodes and limited practicability. Here, metal-organic framework (MOF) containing open-metal sites (OMSs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 36 publications
(61 reference statements)
0
45
0
Order By: Relevance
“…Excitingly, the Li/Na anode morphology with the PHGE electrolyte was more uniform, with only a rough surface without dendrite growth observed after full cycling (Figure c). It is worth mentioning that dendrite growth seriously shortens the battery cycle life and has safety hazards. , These results showed that the high Li + /Na + transference number of the PHGE electrolyte and the anion immobilization by HKUST-1 nanoparticles were the factors limiting dendritic growth and promoting uniform Li/Na deposition, which greatly improved the electrochemical performance of LMBS and SMBs. ,, The performance of LMBs and SMBs based on the PHGE electrolyte was better than that reported in the recent literature (Tables S4 and S5 and Figure d,e).…”
Section: Results and Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Excitingly, the Li/Na anode morphology with the PHGE electrolyte was more uniform, with only a rough surface without dendrite growth observed after full cycling (Figure c). It is worth mentioning that dendrite growth seriously shortens the battery cycle life and has safety hazards. , These results showed that the high Li + /Na + transference number of the PHGE electrolyte and the anion immobilization by HKUST-1 nanoparticles were the factors limiting dendritic growth and promoting uniform Li/Na deposition, which greatly improved the electrochemical performance of LMBS and SMBs. ,, The performance of LMBs and SMBs based on the PHGE electrolyte was better than that reported in the recent literature (Tables S4 and S5 and Figure d,e).…”
Section: Results and Discussionmentioning
confidence: 64%
“…The ionic transference numbers of PHGE-Li and PHGE-Na electrolytes were as high as 0.61 and 0.60, respectively, and much higher than the other two electrolytes (Figure S2). This might have been due to anion immobilization by HKUST-1 nanoparticles, which promoted the preferential transport of Li + /Na + . , The high ion transference number was expected to reduce the polarization inside the battery and reduce side reactions . The electrochemical stability window (ESW) of the electrolyte was measured using linear sweep voltammetry (Figure e,f).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 43 ] It is reported that the lithium transference number of liquid electrolytes is generally less than 0.3, which aggravates the growth of lithium dendrites. [ 44 ] The t Li + value of PPPL is as high as 0.59, while that of PPP and PPL is only 0.28 and 0.35, respectively (Figure 2g–i). The significant improvement of PPPL in t Li + can be mainly attributed to the combined effect of inorganic LLZTO, organic framework and the strong polarity of PMVE‐MA, which can attract the anion ODFB – .…”
Section: Resultsmentioning
confidence: 99%
“…[42] The inertness of MOFs also benefits the interfacial stability of GEs. [43] To name a few, HKUST-1, [42] Mg-MOF-74, [44] UiO-66, [45] and ZIF-8 [46] have been used as nanofillers to improve the ionic conductivity and Li + transference number. Despite the satisfactory ionic conductivity >1 mS cm −1 , these MOF-filled GEs exhibit moderate Li + transference numbers (≈0.6), meaning that more efforts are necessary to further improve the Li anode stability and then extend the battery lifespan.…”
Section: Introductionmentioning
confidence: 99%